Pitfall Traps Minsrepresent the Terricoline Fauna in a Tropical Forest: A Novel Evaluation - Siegert, Anke; Curio, Eberhard (Silliman Journal, 2023)
A critical evaluation of trapping efficiency in two rainforest biomes (primary vs. secondary forest) using a new combination of direct observation of events at widely used Barber pitfall traps, dry (= live) trapping, and the deployment of a trap funnel ensuring maximum retaining efficiency was conducted in the NW Panay Peninsula, Philippines. The omission of any preservative fluid ensured that neither attracting nor repelling odors confounded the results. The release of the live catch ensured that there was no depletion of local fauna and, hence, no 'digging-in' effect. Collectively, 12 traps, placed in identical linear arrays of six, in both types of forest each, yielded a total catch of 255 terricoline invertebrates (Oligochaeta, amphipod Crustacea, Myriapoda, Araneae, lnsecta and their larvae). Two separate hours of direct observation per day of events of approach by terricolines to three of the traps in each habitat yielded a catch of a mere 21% of all individuals which made contact with a trap, or entered the outer funnel wall, but then turned away or exited and left. For the same reason, traps also failed qualitatively to portray the terricoline fauna by not trapping a formicine species of ant and an araneid spider. Hence, even with a maximum of precautionary naturalness, pitfall trapping grossly fails to reflect a terricoline community in terms of species abundance and composition.